Billions to Trillions : Ideas to Actions - Kim, Jim Yong (2016)
Remarks delivered by Jim Yong Kim, President of the World Bank Group, focus on moving from ideas to action for mobilizing trillions of dollars needed for development. He notes that with the end of the Millennium Development Goals and the introduction of the Sustainable Development Goals comes an opportunity to make important changes in how we approach development. He suggests exploring ways to use our shareholder capital, innovative financing solutions, knowledge, and convening power to catalyze and crowd-in trillions of public and private sector dollars. The flexibility of the MDB model, which allows us to leverage these investments through the development of innovative solutions to global challenges. To go from billions in official assistance to trillions in investments, we will have to push even further our willingness to collaborate through creative partnerships.